A three-dimension terminal simulation tool based on transfinite element method - Yang, Siyi; Wang, Hao; Xu, Li; Chen, Muyi; Liu, Bingqi; Liu, Hangxin; Li, Bin (Frontiers in Physics, 2022)
In the design of high-speed interconnection systems, it is often necessary to evaluate signal integrity and electromagnetic interference performance by extracting terminal network parameters and differential and common mode network parameters. However, in a multi-conductor transmission line, the characteristic parameters related to different conductors, which named terminal in terminal theory, are couped together in traditional model network parameters and could not be extracted directly. Therefore, in this paper, a three-dimension terminal simulation tool based on transfinite element method is developed to solve this problem. The vector finite element method is combined with the transfinite element method, and the electric field of the truncation surface is approximated by the expansion of the truncation surface mode function. As far as we know, the combination of the transfinite element method and the terminal theory is proposed for the first time. The terminal simulation tool has a human-computer interaction interface, as well as functions such as modeling, mesh generation, solution setting, and post-processing result display, which can accurately obtain the terminal network parameters and differential and common mode network parameters. Numerical examples are given to demonstrate the accuracy and efficiency of the developed tool compared with the results from HFSS.